Identification of terroirs in the Robertson valley for Chardonnay and Shiraz : a focus on soil and roots - Erazo-Lynch, Leonardo (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScAgric (Viticulture and Oenology))--University of Stellenbosch, 2011.